Precooling methods and their effects on athletic performance - Ross, M.; Abbiss, C.; Laursen, P.; Martin, D.; Burke, L. (Sports Medicine, 2013)
Precooling is a popular strategy used to combat the debilitating effects of heat-stress-induced fatigue and extend the period in which an individual can tolerate a heat-gaining environment. Interest in precooling prior to sporting activity has increased over the past three decades, with options including the application (external) and ingestion (internal) of cold modalities including air, water and/or ice, separately or in combination, immediately prior to exercise. Although many studies have observed improvements in exercise capacity or performance following precooling, some strategies are more logistically challenging than others, and thus are often impractical for use in competition or field settings.